Serotyping And Drug Sensitivity Of Escherichia Coli Isolated From Diarrhoeic And Nondiarrhoeic Calves - Bhuyan , J.; Kalita , D.N. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
One hundred forty five fresh faecal samples were collected randomly from both diarrhoeic and nondiarrhoeic calves below 35 days of age from Guwahati and nearby areas of Assam, of which 90 (62.07%.) samples were found to be positive for E.coli infection. The 'O86' serogroup in diarrhoeic calves and the O172 serogroup in nondiarrhoeic calves was found to be predominant. The drug sensitivity pattern of the isolated organisms to 12 antimicrobial agents revealed that the isolated and tested strains of Escherichia coli were highly sensitive to gentamicin, nalidixic acid and norflxacin, followed by neomycin, chloramphenicol, amoxicillin, streptomycin, furazolidone, tetracycline and co-trimoxazole, while they were resistant to ampicillin and sulfadiazine.
Keywords: Calf; Antibiogram; Drug sensitivity; Serogroup